2021
DOI: 10.3390/ijgi11010002
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Urban Vitality on Streets: Spatial Patterns and Influence Factor Identification Using Multisource Urban Data

Abstract: Urban vitality is a key indicator for measuring urban development. This topic has been trending in urban planning and sustainable development, and significant progress has been made in measuring single indicators of urban vitality based on parcel or block units. With the continuous development of smart sensing technology, multisource urban data are becoming increasingly abundant. The application of such data to measure the multidimensional urban vitality of street space, reflecting multiple functions of an urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…Conversely, streets with high social vitality values had both high and low economic vitality values, indicating that, despite high people flows in the street, there was still a low level of economic vitality and a mismatch with social vitality. This finding is consistent with previous studies [7]. Previously, it was believed that areas with high cultural vitality were concentrated in urban centers, but streets with high cultural vitality values did not have high social and economic vitality values.…”
Section: Analysis Of the Spatial Characteristics Of Street Vitality I...supporting
confidence: 93%
See 1 more Smart Citation
“…Conversely, streets with high social vitality values had both high and low economic vitality values, indicating that, despite high people flows in the street, there was still a low level of economic vitality and a mismatch with social vitality. This finding is consistent with previous studies [7]. Previously, it was believed that areas with high cultural vitality were concentrated in urban centers, but streets with high cultural vitality values did not have high social and economic vitality values.…”
Section: Analysis Of the Spatial Characteristics Of Street Vitality I...supporting
confidence: 93%
“…The study of street vitality plays a key role in optimizing and improving urban vitality, and also provides a new perspective for the investigation of urban vitality, and can provide important theoretical reference significance for subsequent street planning research. Street vitality is an indicator of the level of urban development and a comprehensive embodiment of the quality of urban development [7]. Jacobs [8] was the first to introduce the concept of street vitality, rethink modern urban planning led by streets, and propose a theory of urban diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Following the principles of objectivity, typicality, and data availability, a total of five indicators were selected as the influencing factors of the spatial variation of the level of coupling coordination between mixed land use and urban vitality by using a combination of literature analysis [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and expert consultation methods ( Table 5 ). (1) Economic level: economic development determines the concentration of various city resources and factors, which profoundly affects the level of mixed land use and urban vitality, characterized by GDP per capita.…”
Section: Resultsmentioning
confidence: 99%
“…These attempts to study urban vitality have demonstrated the feasibility of analytical methods that use big data to reflect the characteristics of population activity as a means to obtain an accurate distribution of urban vitality [ 21 ]. They equally prove the validity of geo-information data in the analysis of the spatial pattern and vitality of streets [ 22 ]. However, current studies on urban vitality tend to neglect the interaction of vitality and built-up environment [ 23 ] and few have provided a categorization framework for vitality understanding, which limits the creative value of vitality analysis for urban design [ 24 ].…”
Section: Introductionmentioning
confidence: 93%